2021
DOI: 10.1080/03007995.2021.1901679
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19-related changes in media consumption on public knowledge: results of a cross-sectional survey of Pennsylvania adults

Abstract: Objective: During the COVID-19 pandemic, Americans have increasingly relied on internet versus television news. The extent to which this change in health news consumption practice impacts health knowledge is not known. This study investigates the relationship between most trusted information source and COVID-19 knowledge. Methods: A cross-sectional online survey was sent to a convenience sample from a list of adults on a central Pennsylvania health system's marketing database 25-31 March 2020. Respondents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…However, source of the information matters, participants with good knowledge had a higher tendency to vaccine acceptance. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…However, source of the information matters, participants with good knowledge had a higher tendency to vaccine acceptance. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…Three separate studies of vaccine hesitancy were conducted in nearby Central Pennsylvania, though all reported significant lack of diversity among sociodemographic groups. Study populations were comprised of 92%-97% non-Hispanic white adults, with the majority having attained high income and educational levels (11)(12)(13). In our study demographic, majority of participants identified as Black or African American (53%), women (81%), having finished high school and/or some post-graduate work but not college (65%), and in the 25-64 age range (78%), largely representative of known Turtle Creek community demographics (7).…”
Section: Discussionmentioning
confidence: 99%
“…Trusted sources of general medical information and vaccine-specific information are strong predictors of health literacy (11,12,(18)(19)(20) and were assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The study called for the use of government health websites, as well as monitoring and correcting misinformation presented by other sources (eg, Facebook) in order to maximise information dissemination and compliance with COVID-19-related public health recommendations. 39 …”
Section: Discussionmentioning
confidence: 99%